2013
DOI: 10.1063/1.4827024
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of geometric parameters from PBE-based doubly hybrid density functionals PBE0-DH, PBE0-2, and xDH-PBE0

Abstract: We present a systematic investigation on the optimized geometric parameters for covalently bonded molecules, nonbonded intermolecular complexes, and transition state structures from three PBE (Perdew-Burke-Ernzerhof)-based doubly hybrid (DH) density functionals, namely PBE0-DH, PBE0-2, and xDH-PBE0. While the former two are the B2PLYP-type of DH functionals with no fit parameters, the latter is the XYG3-type of DH functional (xDH for short) with three fit parameters, whose energy expression is constructed by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 97 publications
3
27
0
Order By: Relevance
“…Also, with only two exceptions, the combination of these methods with dispersion‐corrections has not yet been investigated. Studies involving geometries, atomization energies, barrier heights and also an analysis of parts of the GMTKN30 test set (all without dispersion corrections) have revealed that these methods are definitely better than the underlying B3‐LYP and PBE0 hybrids, but a closer inspection of the results shows that the more empirical B2‐PLYP, B2GP‐PLYP, PWPB95, and the DSD functionals seem to be overall more robust and accurate . Nevertheless, the herein reviewed derivation is of academic value and helps emphasizing the theoretical justification for double‐hybrid functionals.…”
Section: Further Developmentsmentioning
confidence: 87%
“…Also, with only two exceptions, the combination of these methods with dispersion‐corrections has not yet been investigated. Studies involving geometries, atomization energies, barrier heights and also an analysis of parts of the GMTKN30 test set (all without dispersion corrections) have revealed that these methods are definitely better than the underlying B3‐LYP and PBE0 hybrids, but a closer inspection of the results shows that the more empirical B2‐PLYP, B2GP‐PLYP, PWPB95, and the DSD functionals seem to be overall more robust and accurate . Nevertheless, the herein reviewed derivation is of academic value and helps emphasizing the theoretical justification for double‐hybrid functionals.…”
Section: Further Developmentsmentioning
confidence: 87%
“…However, for the last term, we need the so‐called U matrix to allow orbital mixing upon perturbation, which can only be obtained by solving coupled‐perturbed (CP)‐KS equations via the Z‐vector method . For an xDH functional, attention has been paid to its nonvariational nature that energy is evaluated with a DH functional based on orbitals and density from the other SCF functional, giving rise to extra terms as compared to the standard theories . Hence for response properties calculated by xDH functionals, perturbation on energy from the DH functional is related to the relaxation of orbitals from the SCF functional by solving the CP‐KS equations …”
Section: The Xyg3 Type Of Doubly Hybrid Functionalsmentioning
confidence: 99%
“…In the followed sections, we will discuss the theoretical background of the DH functionals, briefly reviewing the adiabatic connection (AC) formalism, coordinate scaling relations, and Görling–Levy (GL) perturbation theory . General performance of the DH functionals will then be summarized, not only for energies, but also for structures. In particular, we will present the fractional charge behaviors of the DH functionals, examining the SIEs, the delocalization errors and the deviation from the linearity condition, as well as their effects on the predicted ionization potentials, electron affinities and fundamental gaps, providing a theoretical rationale for the observed good performance of the xDH functionals.…”
Section: Introductionmentioning
confidence: 99%
“…However some exceptions can be found in the literature, 18-20 mainly concerning specific cases, like transition state structures, [21][22][23] weakly bound interacting complexes, 24,25 conjugated polymers 26 or H-bonds. 27 Most of these latter studies showed that…”
Section: -8mentioning
confidence: 99%